NK-DC Crosstalk in Immunity to Microbial Infection - Rony Thomas; Xi Yang (2016)
The interaction between natural killer (NK) cell and dendritic cell (DC), two important cellular components of innate immunity, started to be elucidated in the last years. The crosstalk between NK cells and DC, which leads to NK cell activation, DC maturation, or apoptosis, involves cell-cell contacts and soluble factors. This interaction either in the periphery or in the secondary lymphoid organs acts as a key player linking innate and adaptive immune responses to microbial stimuli. This review focuses on the mechanisms of NK-DC interaction and their relevance in antimicrobial responses. We specifically aim to emphasize the ability of various microbial infections to differently influence NK-DC crosstalk thereby contributing to distinct adaptive immune response.